Interpolation and Approximation of Continuous Functions with Values in the Unit Interval. (17th February 2019) - Kashimoto, M. S.
Abstract: We give applications of a Stone-Weierstrass type theorem concerning uniform density of certain subsets with property V in and establish a simultaneous interpolation and approximation result in when X is a compact Hausdorff space.